2007
DOI: 10.1007/s10886-007-9390-2
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Compound Totarol of Thujopsis dolabrata var. hondai Seeds Selects for Fungi on Seedling Root Surfaces

Abstract: Hinoki-asunaro (Thujopsis dolabrata Sieb. et Zucc. var. hondai Makino) is a tree endemic in Japan whose seeds produce several terpenoids. We hypothesized that antifungal compounds in seeds might select for fungi on the root surfaces of T. dolabrata var. hondai seedlings. We examined seed and soil fungi, their sensitivity to methanol extracts of the seeds, the fungi on root surfaces of seedlings grown in Kanuma pumice (a model mineral soil) and nursery soil, and the frequency at which each fungus was detected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Compounds 1 and 9 have also been reported to show antignawing activity and potent larvicidal activity, respectively (Ahn et al, 1995;Lee et al, 1997). Compound 12 (hinokitiol) has been found to show a broad spectrum of biological activities, including antimicrobial activity (Inamori et al, 1993;Sakagami et al, 2000;Takahashi et al, 2001;Morita et al, 2003Morita et al, , 2004Yamaji et al, 2007;Noshita et al, 2009), and was also reported to be a useful agent for skin (Oreal Cosmetic, 1982;Sakai and Tamura, 1989;Akiyama et al, 1994;Baba et al, 1998). Considering that many applications of hinokitiol (12) to skin have been reported and sesquiterpenes (1, 5, 8-11) showed strong antibacterial activities (Table II), basic dermatological research on these compounds seems desirable.…”
Section: Antimicrobial Activity Of Compounds 1-15mentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 1 and 9 have also been reported to show antignawing activity and potent larvicidal activity, respectively (Ahn et al, 1995;Lee et al, 1997). Compound 12 (hinokitiol) has been found to show a broad spectrum of biological activities, including antimicrobial activity (Inamori et al, 1993;Sakagami et al, 2000;Takahashi et al, 2001;Morita et al, 2003Morita et al, , 2004Yamaji et al, 2007;Noshita et al, 2009), and was also reported to be a useful agent for skin (Oreal Cosmetic, 1982;Sakai and Tamura, 1989;Akiyama et al, 1994;Baba et al, 1998). Considering that many applications of hinokitiol (12) to skin have been reported and sesquiterpenes (1, 5, 8-11) showed strong antibacterial activities (Table II), basic dermatological research on these compounds seems desirable.…”
Section: Antimicrobial Activity Of Compounds 1-15mentioning
confidence: 99%
“…hondai Makino (Cupressaceae) is widely distributed in Korea and Japan. This plant contains a number of neutral terpenoids, several acidic phenols, and lignans (Takahashi et al, 2001;Morita et al, 2003Morita et al, , 2004Yamaji et al, 2007;Noshita et al, 2009). In particular, essential oil extracted from T. dolabrata has antimicrobial activity against bacteria, wood-rotting fungi, and plant pathogens and is insecticidal against termites (Takahashi et al, 2001;Yamaji et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hondai Makino (Cupressaceae) is a plant that grows in Korea and Japan. Thujopsis dolobrata contains a number of neutral terpenoids (Takahashi et al, 2001;Yamaji et al, 2007) and several acidic phenols, tropolones, and lignans (Morita et al, 2003;Morita et al, 2004;Noshita et al, 2009). It has been reported that hinokitiol, the major component of Thujopsis dolobrata, has anti-bactericidal and anti-fungal activity (Morita et al, 2002;Morita et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2 Totarol exhibits antiplasmodial activity, 3 antifungal, 4 and antimicrobial activity against several organisms, including Propionibacterium acnes 56 and methicillin-resistant Staphylococcus aureus (MRSA). 5, 7 The mechanism of action by which totarol derives its antimicrobial activity has not been fully elucidated.…”
mentioning
confidence: 99%